2017
DOI: 10.4254/wjh.v9.i6.333
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E for the treatment of children with hepatitis B e antigen-positive chronic hepatitis: A systematic review and meta-analysis

Abstract: AIMTo assess vitamin E efficacy, defined as its ability to induce hepatitis B e antigen (HBeAg) seroconversion, in children with HBeAg-positive persistent hepatitis.METHODSIn July 2016, we extracted articles published in MEDLINE and the Cochrane Library using the following search terms: “chronic hepatitis B”, “children”, “childhood”, “therapy”, “treatment”, “vitamin E”, “tocopherols”, “tocotrienols”. Only randomized controlled trials (RCTs) published in English language were collected.RESULTSThree RCTs met inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…Similarly, supplementation of vitamin E (200 IU/day) did not have a statistically significant effect on lower respiratory tract infections in elderly nursing home residents [97] . However positive effects of vitamin E have been observed in the treatment of chronic hepatitis B in a small pilot RCT, where a significantly higher normalization ofliver enzymes and HBV-DNA negativization, was observed in the vitamin E group [98] .Similar results have been observed in a RCT in the paediatric population, where vitamin E treatment resulted in a higher anti-HBe seroconversion and virological response [99] .…”
Section: Vitamin Esupporting
confidence: 70%
“…Similarly, supplementation of vitamin E (200 IU/day) did not have a statistically significant effect on lower respiratory tract infections in elderly nursing home residents [97] . However positive effects of vitamin E have been observed in the treatment of chronic hepatitis B in a small pilot RCT, where a significantly higher normalization ofliver enzymes and HBV-DNA negativization, was observed in the vitamin E group [98] .Similar results have been observed in a RCT in the paediatric population, where vitamin E treatment resulted in a higher anti-HBe seroconversion and virological response [99] .…”
Section: Vitamin Esupporting
confidence: 70%
“…In a small pilot RCT protective effects of vitamin E have been reported by treatment of chronic hepatitis B [ 112 ]. Similar study in the pediatric population showed that vitamin E supplementation led to a higher anti-HBe seroconversion and viral response [ 113 ]. Suggested contributing mechanisms were the improvement of effective immune synapse formation in naive T cells and the initiation of T cell activation signals, the reduction of prostaglandin E 2 (PGE2) production by the inhibition of COX2 activity mediated through decreasing NO production, and the modulation of Th1/Th2 balance [ 114 ].…”
Section: Nutrients and Bioactive Compoundsmentioning
confidence: 86%
“…Vitamin E supplementation has been proposed as a therapy for chronic hepatitis B with good results (Andreone et al 2001) (Fiorino et al 2017). However, vitamin E and/or multivitamin-mineral supplementation have not presented good results for acute respiratory tract infections in elderly patients (Graat, Schouten, and Kok 2002).…”
Section: Obesity Nutrition and Viral Immune Responsementioning
confidence: 99%